Differentiation of low and high yielding dairy cows based on their body measurements and acoustic features (Indian Journal of Animal Production and Management, 2017)
Vocalization in dairy animals is thought to be one of the best means of conversation between each other  as well as with environment. The present investigation was carried out on 12 lactating crossbred Karan  Fries cows. The vocal signals from these animals were recorded for sufficient time in order to receive 50  complete sound clips. The various acoustic features were extracted in order to establish the relationship  between these and various body related measurements. The yielding capacity of KF crossbred cows was  found to be significantly affected by only their heart girth (P< 0.05) and length of bridge of nose (P< 0.01).  Moreover, among various acoustic features of vocalizations investigated in present study only total energy,  call duration, F5 and mean formant dispersion reflected a significant (P< 0.05) effect on yielding capacity  of KF crossbred cows. Among various body measurements only the heart girth reflected significantly (P
Keywords: Acoustic features; Body measurements; High and low yielders; Karan Fries cows; Vocalization